Redescription of Urophycis brasiliensis (Kaup 1858), a senior synonym of Urophycis latus Miranda Ribeiro 1903 (Gadiformes: Phycidae) - Lemes, Paola C. R.; Loeb, Marina V.; Santificetur, César; Melo, Marcelo R. S. (Zootaxa, 2016)
Urophycis Gill 1864 is a genus of demersal fish composed by eight valid species with anti-tropical distributions in the western Atlantic. Only two species occur in the South Atlantic: U. brasiliensis (Kaup 1858) and U. mystacea Miranda Ribeiro 1903. These species have similar ranges from southeastern Brazil to northern Argentina, but U. brasiliensis occurs in more shallow waters than U. mystacea. Both species are important fishery resources in southern Brazil and Uruguay. Herein, we redescribe U. brasiliensis based on comparison of types and additional specimens, including the description of the Sagitta otolith, formerly place U. latus Miranda Ribeiro 1903 as a junior synonym of U. brasiliensis, and provide an updated map of distribution.